2016
DOI: 10.1016/j.cub.2016.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Integration Windows in Neural Processing and Perception Aligned to Saccadic Eye Movements

Abstract: SummaryWhen processing dynamic input, the brain balances the opposing needs of temporal integration and sensitivity to change. We hypothesized that the visual system might resolve this challenge by aligning integration windows to the onset of newly arriving sensory samples. In a series of experiments, human participants observed the same sequence of two displays separated by a brief blank delay when performing either an integration or segregation task. First, using magneto-encephalography (MEG), we found a shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
148
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(161 citation statements)
references
References 47 publications
10
148
3
Order By: Relevance
“…Both suppression and enhancement are independent of stimulus eccentricity (Knöll et al, 2011) and thus are unlikely generated by spatial attention, which shifts from fixation to saccadic target very early, ϳ300 ms before saccadic onset (Kowler et al, 1995;Deubel and Schneider, 1996;Rolfs and Carrasco, 2012). The perisaccadic suppression and the subsequent enhancement form a cycle of an oscillation at ϳ3 Hz, suggesting that they might be part of a more prolonged oscillation linked to saccadic preparation, similarly to the visual oscillation demonstrated in preparation of an hand action (Tomassini et al, 2015;Benedetto et al, 2016).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Both suppression and enhancement are independent of stimulus eccentricity (Knöll et al, 2011) and thus are unlikely generated by spatial attention, which shifts from fixation to saccadic target very early, ϳ300 ms before saccadic onset (Kowler et al, 1995;Deubel and Schneider, 1996;Rolfs and Carrasco, 2012). The perisaccadic suppression and the subsequent enhancement form a cycle of an oscillation at ϳ3 Hz, suggesting that they might be part of a more prolonged oscillation linked to saccadic preparation, similarly to the visual oscillation demonstrated in preparation of an hand action (Tomassini et al, 2015;Benedetto et al, 2016).…”
Section: Introductionmentioning
confidence: 78%
“…Brain oscillations might be important in binding and integrating sensorimotor information (Engel et al, 2001) via a shared internal oscillator that coordinates the two systems. Recent experiments have shown that voluntary movements can synchronize oscillations of visual performance (Tomassini et al, 2015;Benedetto et al, 2016). Therefore, action not only interferes with perception through a single transient suppression at around movement time (a phenomenon called "motorinduced suppression"), but rhythmically interacting long before and after action execution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the null distribution). This distribution can, for instance, be constructed by repeatedly shuffling performance labels (e.g., "hits" vs "misses") and re-running the original analysis on the permuted datasets (Busch et al, 2009;Dugué et al, 2011;Hanslmayr et al, 2013;Ng et al, 2012;Ronconi et al, 2017;Strauß et al, 2015;ten Oever and Sack, 2015;Wutz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent experimental 18 work provides a completely different perspective onto selective attention, suggesting that spatial 19 attention samples the visual scene rhythmically [20][21][22][23][24][25][26] . These studies report that target detection 20 performance at an attended location fluctuates rhythmically very much like overt sampling processes, such 21 as eye exploration in primates [27][28][29] or whisking in rodents 30,31 . The neural processes at the origin of this 22 rhythmic sampling of space by attention are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%